Universal highly efficient conditional knockout system in Leishmania, with a focus on untranscribed region preservation. (27th January 2020) - Yagoubat, Akila; Crobu, Lucien; Berry, Laurence; Kuk, Nada; Lefebvre, Michèle; Sarrazin, Amélie; Bastien, Patrick; Sterkers, Yvon
Abstract: Trypanosomatids are divergent eukaryotes of high medical and economical relevance. Their biology exhibits original features that remain poorly understood; particularly, Leishmania is known for its high degree of genomic plasticity that makes genomic manipulation challenging. CRISPR‐Cas9 has been applied successfully to these parasites providing a robust tool to study non‐essential gene functions. Here, we have developed a versatile inducible system combining Di‐Cre recombinase and CRISPR‐Cas9 advantages. Cas9 is used to integrate the LoxP sequences, and the Cre‐recombinase catalyses the recombination between LoxP sites, thereby excising the target gene. We used a Leishmania mexicana cell line expressing Di‐Cre, Cas9, and T7 polymerase and then transfected donor DNAs and single guide RNAs as polymerase chain reaction (PCR) products. Because the location of LoxP sequences in the genomic DNA can interfere with the function and localisation of certain proteins of interest, we proposed to target the least transcribed regions upstream and/or downstream the gene of interest. To do so, we developed "universal" template plasmids for donor DNA cassettes with or without a tag, where LoxP sequences may be located either immediately upstream the ATG and downstream the stop codon of the gene of interest, or in the least transcribed areas of intergenic regions. Our methodology is fast, PCR‐based (molecular cloning‐free), highly efficient, versatile, and able to overcome the problems posed by genomic plasticity in Leishmania .